User study and information marketing (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Based on a literature review on the theoretical foundations of information marketing and user studies were selected two master dissertations of a Postgraduate Program in Information Science that addressed user studies as a methodological procedure to understand the relationship between supply and demand. The objective of reporting the results of the two master dissertations was to highlight the alternative approach for these studies focusing on users’ perception as a methodological procedure to study the management of information supply and demand in a digital library and a management information system in an information marketing perspective. Despite the different objectives of the dissertations selected, it is inferred that alternative approach of users studies as a methodological procedure to study the users' perception about information supply and demand is possible. This theoretical and methodological approach to integrate the concepts and principles of information marketing in user studies in the context of management of information supply and demand is significant as a contribution to the knowledge on the subject studied. Keywords: Information Supply. Information Demand. Information Marketing. User Studies. Digital Library. Information System. Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/3114/2400